Nanocatalysis in ionic liquids - Prechtl, Martin H. G. (Weinheim, Germany : Wiley-VCH Verlag, 2016)
Edited and written by renowned experts in the field, this is the first book to reflect the state of the art of nanocatalysis in ionic liquids. Divided into two core areas, the first part of the book describes the different classes of metal nanoparticles as well as their synthesis in ionic liquids, while the second focuses on such emerging issues as the application of such systems to energy and biomass conversion.
Synthesis, Characterization, and Evaluation of Nanocatalysts in Ionic Liquids. Fe, Ru, and Os Nanoparticles / Madhu Kaushik, Yuting Feng, Nathaniel Boyce, Audrey Moores -- Co, Rh, and Ir Nanoparticles / Jackson D Scholten, Muhammad I Qadir -- Ni and Pt Nanoparticles / Carla Weber Scheeren -- Pd Nanoparticles for Coupling Reactions and Domino/Tandem Reactions / Anna M Trzeciak -- Soluble Pd Nanoparticles for Catalytic Hydrogenation / Ran Zhang, Zhenshan Hou -- Au, Ag, and Cu Nanostructures / Abhinandan Banerjee, Robert W J Scott -- Bimetallic Nanoparticles in Ionic Liquids: Synthesis and Catalytic Applications / Isabelle Favier, Emmanuelle Teuma, Montserrat Gomez -- Synthesis and Application of Metal Nanoparticle Catalysts in Ionic Liquid Media using Metal Carbonyl Complexes as Precursors / Raquel Marcos Esteban, Christoph Janiak -- Top-Down Synthesis Methods for Nanoscale Catalysts / Tsukasa Torimoto, Tatsuya Kameyama, Susumu Kuwabata -- Electrochemical Preparation of Metal Nanoparticles in Ionic Liquids / Yasushi Katayama -- Perspectives for Application of Nanocatalysts in Ionic Liquids. Tailoring Biomass Conversions using Ionic Liquid Immobilized Metal Nanoparticles / Srinidhi Narayanan, Jiaguang Zhang, Ning Yan -- Nanoparticles on Supported Ionic Liquid Phases : Opportunities for Application in Catalysis / Pedro Migowski, Kylie L Luska, Walter Leitner -- Photovoltaic, Photocatalytic Application, and Water Splitting / Adriano F Feil, Heberton Wender, Renato V Goncalves.
Includes bibliographical references and index.
Online resource; title from PDF title page (John Wiley, viewed October 11, 2016).
Keywords: Nanochemistry; Catalysis; Ionic solutions; SCIENCE -- Chemistry -- Physical & Theoretical; Catalysis; Ionic solutions; Nanochemistry; Electronic books